Digital Transformation in Pesantren: The Kyai's Role in Improving Educational Services - Bahri, Samsul; Wahid, Abd Hamid; Najiburrahman, Najiburrahman (Nurul Jadid University, 2024)
This research focuses on the role of Kyai in improving the quality of services at the Islamic Boarding School through the adoption of digital technology. Using a qualitative approach, the data collection method is carried out through in-depth interviews, participatory observations, and documentation involving Kyai, students, and pesantren administrators. The study results show that Kyai plays an important role in facilitating the transformation of educational services, including implementing an online registration system that facilitates access to information for parents and students. In addition, using digital platforms increases transparency and efficiency in communication, creating a better relationship between pesantren administrators and the community. The implications of this study show that the support and advocacy of Kyai in utilizing technology can solve modern education's challenges. These findings emphasize the importance of technology integration in pesantren management as a strategic step to improve the quality of education services. This research also provides new insights for developing educational policies in the pesantren environment to become more adaptive and responsive to the needs of the times.